An Analysis of Stephen Sondheim's Into the Woods (1987). - Hueso-Vasallo, Manuel (My University, 2024)
The following practice was carried out in the subject “Literatura Norteamericana II”, in the degree in English Studies at the University of Málaga. The subject was taught and assessed entirely in English. The practice answers what was perceived to be as a gap in the syllabus, in which Broadway musicals were not addressed among the literary creations in the USA during the twentieth century. However, since this is not part of the official syllabus, the task was voluntary and was not part of the subject’s final assessment. Despite this, students found it interesting and grounding for future units, and it awakened them to the possibility of regarding literature as a much ample range of artistic manifestations. The work of Stephen Sondheim was selected for the task because of its lyricism and its intertextuality, which reinforce previous notions addressed through the module.
Keywords: Teatro norteamericano - S. XX; Teatro musical; Sondheim, Stephen - Estudio y enseñanza; Stephen Sondheim; Musical theatre; American drama